Decision-Making Process for Tourism Potential Segmentation: A Case Study Analysis - Fandi Achmad; Irsyad Thalib Abdillah; Husni Amani (School of Industrial and System Engineering, Telkom University, 2023)
The tourism industry is one of the critical sectors driving regional economic development, creatingjobs, and preserving cultural and natural heritage. The Rembang Regency Government is trying todesign a strategy to increase various tourism potentials that support the tourism industry. Stakeholderscannot optimally manage various tourism potentials in Rembang Regency because the support systemfacilities still need to be improved. Potential tourism segmentation based on facility support systems(SSF) can assist the government in carrying out strategies to increase the potential of the tourismindustry. The main objective of this research is to assist stakeholders in the decision-making processand generate policy advice through tourist mapping results, reducing large-scale tourism industryproblems to a scale that can be understood and acted upon in successful tourism industry marketing.Methods in data collection using literature study and observation with accidental sampling todetermine as many as 20 tours. The K-Means method was chosen to classify tourism potential inRembang Regency, Central Java, Indonesia. The results showed three potential tourism clusters inRembang Regency based on Support System and Facilities (SSF) covering telecommunication, powersource, transportation, waste management, location, clean water source, supporting industry, spatial,hospitality, safety, and security. The results of this study can be used in designing decision-makingstrategies by stakeholders to improve the tourism industry. Increasing the potential of each touristcluster by stakeholders has its advantages and disadvantages.